PERANAN GURU PAI DALAM MENYUKSESKAN PENDIDIKAN KARAKTER - sarifa suhra, sarifa (An - Nisa`, 2016)
This paper examines the role of teacher Islamic religion in the success of character education. One of the main factors that determine the quality of education in a country is the teacher. Master who are in the frontline in creating quality human resources. Teachers dealing directly with students in the classroom through the learning process. In the hands of teacher will produce quality students, both academically, skills (skills), emotional maturity, and moral and spiritual. The success of character education teachers do this through three main tasks both in professional fields, humanitarian tasks and duties in the areas of society. Tasks include educating teachers as a profession, teaching, and training. Educating means to continue and develop the values of life. To teach is to continue and develop science and technology. While train skill means developing skills in students